ANALISIS KRITERIA KETUNTASAN MINIMAL (KKM) DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Yusi Tri Hastuti; Sri Haryati (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The establishment of Minimum Competency Criteria (KKM) is one of the essential elements in the educational evaluation system in Indonesia. KKM serves as a reference for determining the level of students’ competency achievement and helps teachers identify further learning needs. This study aims to analyze the implementation of KKM in learning practices, the factors influencing its determination, and its implications for the evaluation process and the improvement of education quality. The method used in this study is descriptive qualitative, with data collected through interviews, documentation, and literature review. The analysis results indicate that KKM is often determined without optimal consideration of the complexity of the material, school support capacity, and the characteristics of the students. Furthermore, improper implementation of KKM may lead to discrepancies between evaluation results and students’ actual abilities. Therefore, a comprehensive understanding and collaboration among stakeholders are necessary in the establishment and implementation of KKM so that the learning evaluation can be conducted objectively and effectively to support the holistic achievement of student competencies.